Nutrients and carbon fluxes in the estuaries of major rivers flowing into the tropical Atlantic - Araujo, Moacyr; Noriega, Carlos; Lefèvre, Nathalie (Frontiers in Marine Science, 2014)
Knowledge of the seasonal variability of river discharge and the concentration of nutrients in the estuary waters of large rivers flowing into the tropical Atlantic contributes to a better understanding of the biogeochemical processes that occur in adjacent coastal and ocean systems. The monthly averaged variations of the physical and biogeochemical contributions of the Orinoco, Amazon, São Francisco, Paraíba do Sul (South America), Volta, Niger and Congo (Africa) Rivers are estimated from models or observations. The results indicate that these rivers deliver approximately 0.1 Pg C yr-1 in its dissolved organic (DOC 0.046 Pg C yr-1) and inorganic (DIC 0.053 Pg C yr-1) forms combined. These values represent 27.3% of the global DOC and 13.2% of the global DIC delivered by rivers into the world’s oceans. Estimations of the air-sea CO2 fluxes indicate a slightly higher atmospheric liberation for the African systems compared with the South American estuaries (+10.67 mmol m-2 day-1 and +5.48 mmol m-2 day-1, respectively). During the high river discharge periods, the fluxes remained positive in all of the analyzed systems (average +128 mmol m-2 day-1), except at the mouth of the Orinoco River, which continued to act as a sink for CO2. During the periods of low river discharges, the mean CO2 efflux decreased to +5.29 mmol m-2 day-1. The updated and detailed review presented here contributes to the accurate quantification of CO2 input into the atmosphere and to ongoing studies on the oceanic modeling of biogeochemical cycles in the tropical Atlantic.